Comparative Effectiveness of and Maternal Acceptability with Cervical Ripening using Cervical Massage Versus Membrane Sweep (CEASELESS): A Randomized Controlled Trial - TMSSB, Madugalle; DMCS, Jayasundara (Archives of Clinical and Biomedical Research, 2022)
Methods: This randomized controlled non-blinded clinical trial conducted at a leading tertiary obstetric care unit in Colombo, Sri Lanka, compared the maternal acceptability and effectiveness of membrane sweep (MS) and cervical massage (CM) in ripening uterine cervix to avoid formal induction of labour. MS, CM, and control (C) groups had 104, 106 and 102 women after randomization. Primiparous women underwent either MS or CM at 39th and 40th weeks while multiparous women underwent at 40th week of gestation only. All were followed up until 24 hours postpartum. 100, 102 and 101 women in MS, CM and C groups respectively were included in the analysis. Results: Overall, MS significantly improved Modified Bishop’s Score (MBS) to ≥7 compared to C (p=0.0310) but not compared to CM (p=0.2639). There was no significant improvement of MBS after CM compared to C (p=0.2795). Among primiparous (p=0.047) and multiparous (p=0.038) women separately, mean survival times without going into labour (MBS≥7) were significantly shorter after MS compared to C but not compared to CM. Hospital stay for delivery was less overall after both MS (p=0.0015) and CM (p=0.0197). There were no significant differences between MS, CM and C groups about synthetic oxytocin use, uterine hyperstimulation during labour, emergency cesarean section rate in labour, postpartum hemorrhage, maternal fever, and APGAR score at 5 minutes. Maternal acceptability was assessed using a validated questionnaire consisting of 4 Likert scale items (S-CVI = 0.875; Cronbach’s Alfa= 0.876). Maternal acceptability score of CM was significantly higher than that of MS during overall analysis as well as during subgroup analysis according to parity (p=0.0011). Conclusions: MS is an effective adjunct to induction which ripens cervix, prevents formal induction